2014
DOI: 10.1177/0146167214554956
|View full text |Cite
|
Sign up to set email alerts
|

Self-Affirmations Provide a Broader Perspective on Self-Threat

Abstract: We present an "affirmation as perspective" model of how self-affirmations alleviate threat and defensiveness. Self-threats dominate the working self-concept, leading to a constricted self disproportionately influenced by the threat. Self-affirmations expand the size of the working self-concept, offering a broader perspective in which the threat appears more narrow and self-worth realigns with broader dispositional self-views (Experiment 1). Self-affirmed participants, relative to those not affirmed, indicated … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

5
138
2

Year Published

2015
2015
2024
2024

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 122 publications
(145 citation statements)
references
References 57 publications
5
138
2
Order By: Relevance
“…We propose that even secular rituals may provide a sense of meaning and perspective, allowing people to expand their working self-concept beyond the threatened domain (e.g., Critcher & Dunning, 2014). Finally, a fourth possibility is that rituals function as a type of placebo (e.g., Crum & Langer, 2007).…”
Section: Rituals Reduce Anxietymentioning
confidence: 98%
“…We propose that even secular rituals may provide a sense of meaning and perspective, allowing people to expand their working self-concept beyond the threatened domain (e.g., Critcher & Dunning, 2014). Finally, a fourth possibility is that rituals function as a type of placebo (e.g., Crum & Langer, 2007).…”
Section: Rituals Reduce Anxietymentioning
confidence: 98%
“…We included an additional control condition "Non-Affirmation" in which participants wrote why their 9th ranked value may be important to someone else. Recent work has suggested potential problems with this control technique (e.g., Critcher, Dunning, & Armor, 2010;Critcher & Dunning, 2015). Given our hypotheses regard comparisons between Affirmation and Control, we report only participants from the Affirmation or Control conditions in the main text.…”
Section: Methodsmentioning
confidence: 99%
“…In fact, Critcher and Dunning (2015) demonstrated that affirming the self reduces defensiveness in the face of threat precisely because it expands the working self-concept and directs attention away from the threatened domain. We posit that a group-affirmation manipulation, in contrast, may directly activate that group's self-aspect or social identity, making any constructs associated with that group psychologically predominant.…”
Section: Group-affirmationmentioning
confidence: 99%